The Effect of Ajwa Dates Fruit Extract (Phoenix dactylifera L.) on the Creatinine Levels in White Rats (Rattus norvegicus) Induced by Meloxicam Toxic Doses - Yuliani Suparmin; Risha Catra Pradhany; Musdalifah Musdalifah; Dian Fatmawati; Nur Afzah Zainuddin; Eka Nurdiana (Jurnal Riset Veteriner Indonesia (Journal of The Indonesian Veterinary Research), 2022)
Meloxicam is an NSAID (non-steroidal anti-inflammatory drug) which is an antipyretic analgesic drug as well as a non-steroidal anti-inflammatory drug that is widely used by the public, including pet owners, in treating their favorite animals without advice from a veterinarian. The use of meloxicam in excessive doses can trigger kidney damage. Based on related research, meloxicam can cause cell death due to nephrotoxicity. Ajwa dates have the highest antioxidant activity among other types of dates, suppress lipid peroxidation, prevent cell damage, and have nephroprotective abilities. The aim of this study was to determine the effect of giving ajwa date fruit extract on creatinine levels of male wistar rats induced by toxic dose of meloxicam. This research is an experimental research with the research design used is the Pre Test-Post Test Design Group. The total sample used was 24 male wistar rats which were divided into 4 groups, namely the negative control group (K1) which was given 1% Na CMC on days 1-18, the positive control group (K2) which was given meloxicam 30mg/kgBW on day 1- 4 and 1% Na CMC on days 5-18, treatment group 1 (K3) was given meloxicam 30mg/kgBW on days 1-4 and ajwa date fruit extract 150mg/kgBW on days 5-18, treatment group 2 (K4) given meloxicam 30 mg/kg body weight on days 1-4 and ajwa date fruit extract 300 mg/kg body weight on days 5-18. Blood sampling was carried out on day 19 to measure creatinine levels. The results of data analysis using the Independent T-Test test for groups K1 and K2 were P < 0.05, which means that there is a statistically significant relationship between the administration of meloxicam and the increase in creatinine levels. The results of data analysis using the independent T-Test test for the K2 group with K3 and K4 were P<0.05, which means that there is a statistically significant relationship between the administration of ajwa date fruit extract and the decrease in creatinine levels of rats given a toxic dose of meloxicam. Keywords: Ajwa dates, creatinine, meloxicam, nephroprotective, white rat